Steel Steady: Community-Based Learning in TVET to Promote Civic Engagement - Firdaus Sariman; Nabil Fikri; Azme Budiman; Sirhajwan Idek; Dayang Siti Khatijah Awang Damit; Lumang Lang (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This project was intended to educate, enable and empower Keningau youth from both technical and vocational education and training (TVET) and mainstream backgrounds to contribute to the community through a building repair and upgrade project. Repair and maintenance in any manmade structure are always necessary but there are many variables which include regularly scheduled maintenance, lack of skilled manpower and limited funding can hinder such routine. Hence, this community project known as Steel Steady mobilized youth volunteers who were essentially students from Keningau Vocational College as well as other schools in Keningau, Sabah, to learn the basics of welding and take part in a building repair and upgrade at a chosen location. The volunteers were required to answer community-based learning (CBL) and civic engagement instruments upon completing the project to determine their overall perception on their experience as volunteers in the community project and to determine the level of influence that each dimension had on their civic engagement. The results from descriptive statistics and multiple regression analysis on their responses suggest that the respondents had positive experience from the project based on the four dimensions of CBL; teamwork, participation, reflection and leadership. These four dimensions strongly influenced their sense of civic engagement.  This implies that CBL is a highly plausible approach in cultivating a sense of awareness, empathy and responsibility of youths towards their community’s needs.